Challenging Hegemony: Fransen van de Putte's Advocacy for Alternative Colonial Policies in Aceh, 1873-1885 - Ahmad Muhajir (Mahesa Research Center (PT. Mahesa Global Publishing), 2024)
This study aims to analyse the role of Fransen van de Putte in advocating for an alternative approach to Dutch colonial policy in Aceh during the period 1873-1885, and identifies the factors influencing his efforts. The focus of this research lies in the criticisms and alternatives proposed by Fransen van de Putte against the Dutch government’s aggressive strategy in Aceh. This study employs a historical method with a social science approach and Antonio Gramsci’s theory of hegemony as its analytical framework. The primary sources include Fransen van de Putte’s speeches compiled in Atjeh: Parlementaire Redevoeringen van I. D. Fransen van de Putte van Februari 1873 – December 1885. Secondary sources consist of books and scholarly journal articles. The findings reveal that, despite being marginalised, Fransen van de Putte consistently voiced criticism and offered alternatives to the Dutch colonial policy in Aceh. However, he faced significant challenges in challenging the hegemonic dominance of aggressive narratives in the Dutch parliament. This research provides new insights into the political dynamics in the Netherlands during the Aceh War and the role of individuals in challenging hegemony, particularly within the context of colonialism.